Development of MATLAB code for differential microstrip antennas - Yang, Xuehao (2017)
The modern communication systems rely fundamentally on the information transmission techniques through electromagnetic waves and in those systems, antenna is one of the most essential components which can be used to convert between radio waves and electric power. More specifically, among different structures of antennas, microstrip antennas are of increasing popularity due to its properties of low-cost, low-weight, low-profile and ease of fabrication. The purpose of this project is to develop a program in the MATLAB environment to reduce the computational complexity in the designing process of differential microstrip antennas. Usually, the analysis of microstrip antennas is performed based on different models such as the transmission-line model and the cavity model. To further simplify the analysis and designing process, a computer-aided-design (CAD) model is introduced and each differential microstrip antenna design parameter can be calculated by applying different CAD formulas. This differential microstrip design program is capable of providing guidance and helping designers determine parameters for desired characteristics in the designing process by providing calculated results as well as a tendency plot based on the user input.